ROS-responsive ADPH nanoparticles for image-guided surgery - Sun, Kangjun; Xu, Ruitong; Xue, Bingyan; Liu, Pengfei; Bai, Jianan; Tian, Ye; Li, Xiaolin; Tang, Qiyun (Frontiers in Chemistry, 2023)
In recent years, organic fluorescent probes with tumor microenvironment (TME)-responsive fluorescence turn-on properties have been increasingly used in imaging-guided tumor resection due to their higher signal-to-noise ratio for tumor imaging compared to non-responsive fluorescent probes. However, although researchers have developed many organic fluorescent nanoprobes responsive to pH, GSH, and other TME, few probes that respond to high levels of reactive oxygen species (ROS) in the TME have been reported in imaging-guided surgery applications. In this work, we prepared Amplex® Red (ADHP) with excellent ROS response performance as an ROS-responsive nanoprobe and studied its application in image-guided tumor resection for the first time. To confirm whether the nanoprobe can be used as an effective biological indicator to distinguish tumor sites, we first detected 4T1 cells with the ADHP nanoprobe, demonstrating that the probe can utilize ROS in tumor cells for responsive real-time imaging. Furthermore, we conducted fluorescence imaging in vivo in 4T1 tumor-bearing mice, and the ADHP probe can rapidly oxidize to form resorufin in response to ROS, which can effectively reduce the background fluorescence signal compared with the single resorufin probe. Finally, we successfully carried out image-guided surgery of 4T1 abdominal tumors under the guidance of fluorescence signals. This work provides a new idea for developing more TME-responsive fluorescent probes and exploring their application in image-guided surgery.